Old Iraqi pottery and aesthetic connotations (B,M example) - Hameed, شيماء مقداد (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
Historical studies have confirmed that the Iraqi arts، since ancient times، are among the oldest arts، which were and still carry aesthetic characteristics and connotations concerned with the ancient Iraqi civilization (the Mesopotamian Civilization)، including ceramics، sculpture، painting، and others، which are now known as plastic arts.Some pottery products have been updated while retaining their attributes، symbols، and aesthetic connotations. The connotations in pottery (ceramics) have their realistic and life-specific significance، including what pertains to humans، animals، plants، and geometric shapes. As for the aesthetics of ancient Iraqi pottery، it has significance since man began making pottery before history، so the drawings on pottery، it has an indication، including what indicates the continuity of life، with the presence of women’s drawings on deeds or deities، indicating religious beliefs and others. The current research included four chapters. Where the research included the first chapter، the research problem and the need for it، and the aim of the research، which includes identifying the aesthetic significance of pottery (ceramics). The limits of the research include prehistoric ceramics، while the second chapter included the theoretical framework and previous studies، if any. Prehistory، and the third chapter included the research community and samples، the research tool and the analysis of samples، and the fourth chapter included the results، conclusions، recommendations and proposals، and that the research took the descriptive method.